Use of furosemide stress test for edema control and predicting acute kidney injury in children with nephrotic syndrome - Kalra, Suprita; Sood, Amit; Narayan, K Venkat; Gupta, R K (Indian Journal of Child Health, 2017)
Background: Furosemide stress test (FST) involves measurement of 2?h urine output after giving 1 mg/kg of furosemide in clinically euvolemic patients and has been shown to identify those with severe and progressive acute kidney injury (AKI). Objectives: To assess whether using FST could help in deciding whether to give diuretics only, or combination of diuretics with albumin infusion, in children with nephrotic syndrome with edema to prevent AKI. Materials and Methods: This prospective, pilot cohort study was conducted on the use of FST to manage edema in children with nephrotic syndrome. Consecutive patients 1–14 years were enrolledfrom October 2016 to April 2017 from the pediatric nephrology outpatient department of a tertiary care center. They were assessed for fluid overload using their present and baseline weight. Patients with fluid overload of ?10% were screened for AKI by measurement of serum urea and creatinine and monitoring of urine output in the next 24 h. Systemic infections were excluded using clinical and laboratory criteria. AKI was defined using the pediatric RIFLE score. Children with fluid overload of ?10% were given intravenous furosemide 1 mg/kg provided; they had no clinical signs of intravascular dehydration or shock. Urine output was measured over thenext 2 h. Children with urine output 10% were analyzed for inclusion in the study. Of them, 11 were excluded and 23 were finally analyzed. 19/23 had urine output >1 mg/kg/h in next 2 h and none had serum creatinine increase >0.3 mg/dl or >150% of the baseline value. 4 had urine output < 1 ml/kg/h. Significant difference was found in the post?FSTheart rate and urea/creatinine ratio between the children who had urine output >1 ml/kg/h and which had < 1 ml/kg/h after furosemide. These children were assumed to be at risk for severe and progressive AKI as per FST and were thereafter given furosemide with albumin to prevent further intravascular dehydration. Conclusion: FST may be used as a bedside test to help identify the children with nephrotic syndrome with intravascular dehydration who are at high risk for AKI and helps rational use of diuretics.